2019
DOI: 10.21475/ajcs.19.13.09.p1557
|View full text |Cite
|
Sign up to set email alerts
|

Phenological study of sugar apple (Annona squamosa L.) in dystrophic yellow latosol under the savanna conditions of Roraima

Abstract: Sugar apple (Annona squamosa L.) is a commercially significant fruit species due to its nutritional qualities. The state of Roraima has excellent soil and climatic conditions for the cultivation of the species. However, no studies on the phenological behavior of this plant have been reported in the literature. In this context, the objective of this work was to investigate the vegetative and reproductive phenological behavior of sugar apple under the savanna conditions of the state of Roraima. The experiment wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…were delayed by 16 and 30 days compared to 'Lessard Thai' and 'Red', respectively. Similar responses to those found in the present study were found by (Pereira et al 2014a), who obtained artificial pollination intervals at 97 days for 'Lessard Thai', 98 days for 'Red' and 115 days for 'Gefner' and with A. squamosa L, respectively (Moura et al 2019a) (Table 1).…”
Section: Phenological Behaviorsupporting
confidence: 90%
See 3 more Smart Citations
“…were delayed by 16 and 30 days compared to 'Lessard Thai' and 'Red', respectively. Similar responses to those found in the present study were found by (Pereira et al 2014a), who obtained artificial pollination intervals at 97 days for 'Lessard Thai', 98 days for 'Red' and 115 days for 'Gefner' and with A. squamosa L, respectively (Moura et al 2019a) (Table 1).…”
Section: Phenological Behaviorsupporting
confidence: 90%
“…Thus, rapid temperature increases in the period of growth and reproductive development may lead to early or delayed flowering. This has been documented to occur in sugar apple grown under semiarid and tropical savanna conditions (Alves Rodrigues et al, 2018;Moura et al, 2020Moura et al, , 2019a.…”
Section: Phenological Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…Fertility conditions are low, which explains the dystrophic properties and minimal productive capacity for agricultural use. These types of soil have low natural fertility due to deficiencies in phosphorus, potassium and calcium (EMBRAPA, 2018;Moura et al, 2019). With dystrophic yellow latosol pedological coverage, lithological and pedological conditions favor the infiltration and percolation of water, hindering the emergence of a dense drainage network (Souza and Silva, 2022).…”
Section: Regardingmentioning
confidence: 99%